ANALISIS POST-HARVEST LOSS PADA OKRA DENGAN METODE OBJECTIVE MATRIX (OMAX) DI PT MITRATANI DUA TUJUH JEMBER - Ida Bagus Suryaningrat; Ferry Julio Prabowo; Winda Amilia (JURNAL AGROTEKNOLOGI, 2020)
Post-harvest loss is a process of the loss or the broken material from production in the field to the food being ready to be consumed. Losses in agricultural or horticultural produce are a major problem in the post-harvest process. Therefore, it was needed to identify the criteria based on the post-harvesting process to know the performance level of each criterion provided. This study was aimed to know the post-harvest loss source in the occurrence of the post-harvest process of okra. This research used Objective Matrix method (OMAX) to evaluate the performance level of each criterion provided. AHP method was also implemented in this research by using the pairwise comparison technique to measure the weight on OMAX and fishbone diagram and to identify causes factors of the okra loss. The research result showed that the picking and weighing process during post-harvest okra have lower performance level and it was not meet the expected target of the company (PT Mitratani Dua Tujuh). Other result of okra loss level was also still far from the expected target of the company. The improvement recommendations were needed to reduce post-harvest okra loss, i.e. increasing supervision by the manager, making removal plot during okra harvesting, and briefing every morning with the okra picker. Keywords: AHP, fishbone diagram, OMAX, post-harvest loss